Methodologycal approach for a study bio-bibliographic scientist - González Freire, José Manuel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
According to the Dictionary of the Royal Spanish Academy defines “Bio-bibliography” as the “Biography of a writer with an enumeration of his works”. But in reality it is much more than that definition. It is a methodological, systematic and scientific study before birth, during and after the death of the author of the study. For many it is the study of life, biography, their professional life, their academic life, their family life, their travels, the truth is that it is this and much more at a synchronous moment in history.